THE INFLUENCE OF EDUCATION/TRAINING (DIKLAT) AND WORK ENVIRONMENT ON EMPLOYEE WORK PERFORMANCE AND ORGANIZATIONAL PERFORMANCE OF THE OFFICE OF PORT MASTER AND PORT AUTHORITY CLASS IV PULANG PISAU - Wiwin Iryani Hasanuddin; Ernawati, Ernawati (Sean Institute, 2022)
The purpose of this study was to prove and analyze the partially significant effect of Education/Training (Training) and Work Environment on Employee Work Performance and Organizational Performance of the Class IV Pulang Pisau Port Authority and Port Authority. The research method used is analytical survey. The type of research is explanatory research. The sample in this study amounted to 36 employees in July 2022. The sample in this study used the total sampling method. The data collection technique used a closed questionnaire that had fulfilled the validity and reliability test requirements, used Path Analysis and the data was analyzed using multiple linear regression analysis.The results showed that education/training (Training) had a significant effect on work performance. The work environment has a significant effect on employee performance. Education/training (Training) has a significant effect on organizational performance. The work environment has no effect on organizational performance. Employee performance has a significant effect on organizational performance. Education/training (Training) has a significant effect on organizational performance with the intervening variable of employee performance. The work environment has a significant effect on organizational performance with the intervening variable of employee performance, the Harbormaster Office and the Class IV Pulang Pisau Port Authority.